Integrative Reasoning Framework (Estudos em Design, 2024)
This article presents a framework called Integrative Thinking, developed to expand limits imposed by an education model that remains fragmented. The concept of Integrative Thinking aims to combine qualities and activate competencies from distinct types of reasoning – scientific, common sense, and design reasoning – to address reality in a broader and more effective way. The framework served as a starting point for creating an educational model that integrates different areas of knowledge and was tested in a pilot course. Although the course received positive feedback, it became clear that the original framework needed improvement, leading to the creation of a canvas tool for future applications. The final considerations highlight design as an interdisciplinary and integrative area, discussing cultural, epistemological, and emotional challenges to adopting more holistic and reflective educational approaches. Future studies should explore the adaptation of models that promote reflective and creative skills, preparing professionals for complex and ever-changing scenarios.